From the Profane to the Sacred: The Healing of Mental Disorders through Inabah Based Practices at Pondok Tetirah Zikir in the Perspective of Mircea Eliade - Jumilah Jumilah (PT. Education Research Center, 2025)
This study examines the spiritual healing system of Pondok Tetirah Dzikir in Yogyakarta, which employs the Inabah method and the dhikr practices of the Qadiriyah Naqsyabandiyah Order to address mental disorders. Using a qualitative approach that integrates phenomenology and religious ethnography, the research explores how guided residents (santri bina) undergo a process of existential recovery through structured rituals such as dhikr, Qur’anic recitation, repentance bathing, and other practices of tazkiyatun nafs. Analysed through Mircea Eliade’s framework of the Sacred and the Profane, the findings reveal that the institution constructs a sacred space and time that facilitates a transition from chaotic profane existence towards a spiritually oriented sacred order. The healing process is shown not merely as a psychological improvement but as a profound religious transformation that restores meaning, spiritual awareness, and harmony in the lives of the residents. This study demonstrates that spiritual-based rehabilitation, grounded in Sufi teachings, holds significant potential in addressing mental health crises in contemporary society.